Effects of paclobutrazol concentration, application techniques and frequency on growth and flowering of Lagerstroemia indica (L.) Pers - Mohammed, Nyan Tahir (2016)
Lagerstroemia indica is an amazing flowering tree but the growth is very fast leading to the deformation of esthetical configurations in a short time. To minimize the problem, the plant can be treated with paclobutrazol (PBZ) to control the growth as previous studies have shown that PBZ can significantly reduce the plant height. The effects of PBZ, a growth retardant on the plant growth and flowering characteristics in L.indica were examined in two greenhouse experiments. In the first experiment, the effects of two application techniques (foliar spray and soil drenching) applied once at four concentrations (0, 1500, 3000 and 4500 mg/L) were evaluated. In the second experiment, the treatments involved application of PBZ delivered in two application frequencies (single and double application) given as soil drench with four concentrations (0, 500, 1000 and 1500 mg/L). Compared to the control plant, PBZ foliar spray and soil drenching reduced plant height by 75% and 90%, respectively. PBZ at 1500 mg/L with double application reduced plant height by 30% of those received single application. PBZ at 3000 mg/L in foliar spray increased the number of flowers by 21%, while PBZ at 1500 mg/L in soil drenching increased the number of flowers by 25% compared to the control plants. In addition, at 3000 mg/L, foliar sprayed-plant produced 49% more leaves compared to the control. Increasing PBZ from 0 to 1500 mg/L via soil drenching with either single or double application increased leaf number by 23%. PBZ application also produced significant effects on chlorophyll a content, total chlorophyll, photosynthesis and transpiration. PBZ at 1500 mg/L with single and double application increased chlorophyll a and total chlorophyll rate by 41% and 34%, respectively, compared to the non-treated plants. The rate of photosynthesis was reduced from 11.11 μmolCO2m-2s-1 to 10.80, 9.30 and 8.86 μmolCO2m-2s-1 as the concentration of PBZ increased from 0 to 1500, 3000 and 4500 mg/L. PBZ was also found to increase the activity of superoxide dismutase (SOD) and catalase (CAT) enzymes by 79% and 360%, respectively when the concentration of PBZ increasing from 0 to 1500 mg/L. PBZ did not affect stomata conductance, leaf mineral contents and peroxidase activity (POD). Overall, results of the present study show that PBZ application produced some positive effects on the growth and flowering of L. indica. PBZ, applied as soil drenching with double application were more effective compared to the foliar spray and single application. Moreover, high PBZ concentration (4500 mg/L) given as soil drenching caused deformation of shoots, buds and delayed formation of the flower buds and reduced the number of flowers.